Analisis Tindak Perundungan Verbal Pada Proses Pembelajaran: Dampak Pada Motivasi dan Prestasi Belajar Siswi Kelas X Studi Kasus di Madrash Aliyah Negeri 2 Situbondo - Cahaya Suksma; Adinda Ramadhanti; Mahendra Agus H.; Miftahus Surur; Dyan Yuliana (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Bullying is an aggressive behavior that threatens and intimidates someone, often driven by an individual's sense of superiority. Research indicates that verbal bullying, especially among teenage girls, is associated with factors such as lack of family attention, social pressure, and exposure to violence through social media. The impact of bullying includes mental health disorders, disruptions in interpersonal relationships, and negative influences on education. Children who are victims of bullying face social challenges, fear of attending school, high absenteeism rates, and academic difficulties. The current era's developments have given rise to cyberbullying, resulting in serious implications for mental and physical health, as well as potential dangers to an individual's safety. Despite experiencing negative effects, some bullying victims still achieve satisfactory academic performance, demonstrating resilience. Solutions involve multi-party interventions, with roles for teachers, counselors, students, and parents. Teachers need to manage interactions in the classroom, counselors provide psychological support, and class discussions create an open environment. Parental involvement is crucial in providing support to students experiencing ostracism. All aim to create an inclusive classroom environment, minimize bullying, and promote positive behavior among young people.